Assessing the performance of cooperatives in post-apartheid South Africa: evidence from the literature - Okem, Andrew Emmanuel (Informa UK Limited, 2023)
While there is growing interest in the literature and policy circles regarding the performance of cooperatives in South Africa, no study has yet synthesised the body of knowledge on how to assess cooperative performance in the country. This paper aims to fill this gap by examining the literature on the performance of cooperatives in post-apartheid South Africa, based on a scoping review of 20 studies published between 1994 and 2021. Most of the reviewed studies adopted a qualitative approach, lacked a clear definition of cooperative performance and standardised metrics/criteria for assessing cooperative performance. The studies often relied on view of study participants to determine the performance of cooperatives. Moreover, the reviewed studies often framed the performance of cooperatives from an economic viewpoint. Clear definition of cooperatives, the development of robust indicators for assessing their performance and greater emphasis on quantitative studies on the performance of cooperatives in South Africa beyond economic and financial indicators is needed.